Alcohol-related intentional nonadherence to antiretroviral therapy among people living with HIV, Cape Town, South Africa. Issue 8 (3rd August 2019) - Kalichman, Seth; Mathews, Catherine; Banas, Ellen; Kalichman, Moira
ABSTRACT: Alcohol use may have significant negative impacts on individuals' ability to remain adherent to antiretroviral therapy (ART), and may also yield other negative psychosocial, health-related, and behavioral outcomes. In addition, false beliefs about the consequences of mixing alcohol with ART use may cause individuals to avoid taking ART when drinking (alcohol-related ART avoidance). Although research conducted in the U.S. and Europe has reported on alcohol-ART avoidance, the current study presents among the first quantitative evidence of alcohol-related intentional ART nonadherence in South Africa. Patients receiving ART from a community clinic in Cape Town ( N = 441) completed anonymous surveys of alcohol use, ART adherence, and alcohol-ART avoidance. Results showed that 292 (66%) participants reported current alcohol use; 25% who use alcohol believed that people who drink should stop taking ART when they are drinking and 24% stop their own ART when drinking. Alcohol-ART avoidance mediated the association between alcohol use and ART adherence. Results were robust when controlling for participant age, gender, current care status, and first- versus second-line ART. We found alcohol-ART avoidance may threaten successful ART in South Africa. Corrective messages that take a harm reduction approach to maximize ART adherence when drinking should be implemented in existing clinical services.